The Effect of Employee Competence and Organizational Culture on Competitive Advantage in the Tourism Industry in Bali - Muhammad Ade Kurnia Harahap; I Wayan Adi Pratama; Ni Desak Made Santi Diwyarthi; Iwan Harsono (West Science Interdisciplinary Studies, 2024)
The tourism industry in Bali represents a dynamic and competitive landscape, where businesses strive to gain and maintain a competitive advantage in a global market. This study investigates the influence of employee competence and organizational culture on competitive advantage within the context of the tourism sector in Bali. A quantitative approach utilizing Structural Equation Modeling (SEM) with Partial Least Squares (PLS) analysis was employed to analyze data collected from 170 participants working in various tourism-related businesses. The findings reveal significant positive relationships between employee competence, organizational culture, and competitive advantage. Employee competence was found to positively influence organizational culture and competitive advantage, while organizational culture was positively associated with competitive advantage. Furthermore, organizational culture partially mediated the relationship between employee competence and competitive advantage. These findings underscore the importance of investing in employee development and fostering a positive organizational culture to enhance competitiveness in the tourism industry in Bali.